Evolution of global inequality in human well–being: a sensitivity analysis. (9th December 2014) - Jordá, Vanesa; Trueba, Carmen; Sarabia, José María
In this paper, we study global inequality in well–being taking as a theoretical benchmark the Human Development Index (HDI), which comprises variables of income, health and education. We use a two–step methodology that involves the construction of a composite index in the first step on which inequality measures are computed. The use of these measures requires making choices on the standardisation of the variables and their weights, the rate of substitution between dimensions and the degree of inequality aversion in the society. We investigate the impact of these choices on the evolution of unweighted inequality over the period 1980–2011. We find the robust result that global inequality in human well–being decreased over the last 30 years.